KONFLIK BATIN DAN KECEMASAN TOKOH GURU ISA DALAM NOVEL JALAN TAK ADA UJUNG KARYA MOCHTAR LUBIS - Nur Reski Wahyuni; Andi Karman; Aslan Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the inner conflict and forms of anxiety experienced by the main character, Guru Isa, in the novel Jalan Tak Ada Ujung by Mochtar Lubis. The main problem of this research focuses on the psychological dynamics of Guru Isa, who lives under the pressure of the Indonesian independence revolution. This study employs a qualitative approach using a descriptive-analytical method. The data analysis is conducted through a literary psychology perspective, particularly Sigmund Freud’s psychoanalytic theory, which includes the structure of personality (id, ego, and superego) and three types of anxiety. The results of the study show that: (1) Guru Isa’s inner conflict arises from the contradiction between his peaceful personal nature and the violent reality of the revolution; (2) three types of anxiety are found in Guru Isa’s character, namely reality anxiety triggered by the real threat of military patrols, neurotic anxiety in the form of irrational fear originating from within himself, and moral anxiety in the form of feelings of guilt and shame due to his failure to meet social expectations as a teacher. This study concludes that Guru Isa’s psychological condition reflects the individual’s psychological pressure in facing an identity crisis and socio-political circumstances.